Apomorphine for Parkinson's Disease. Issue 5 (1st October 2002) - Lees, Andrew; Turner, Kirsten
Abstract : A pomorphine was first used to treat behavioural vices in domesticated farm animals in the nineteenth century and is still used in veterinary medicine. It has had a chequered history in medical therapeutics, being successfully recommended as an emetic, a sedative, a treatment for narcotic and alcohol dependence and most recently for sexual dysfunction and impotence. It was first proposed as a treatment for movement disorders 150 years ago, but this indication was not pursued until the 1950s when Schwab in Boston confirmed its potential (Schwab et al . 1951). Following his demonstration that large doses of dopa improved Parkinson's disease, George Cotzias looked for other dopamine analogues that might have complementary effects and carried out a series of scrupulous and fascinating experiments with apomorphine (Cotzias et al . 1970). These indicated that the effects of the drug, when administered by subcutaneous injection, were potent but short-lived, and that vomiting and postural